DNAH14 variants are associated with neurodevelopmental disorders. Issue 7 (28th April 2022) - Li, Juan; Yuan, Yu; Liu, Chaorong; Xu, Yuchen; Xiao, Neng; Long, Hongyu; Luo, Zhaohui; Meng, Shujuan; Wang, Hua; Xiao, Bo; Mao, Xiao; Long, Lili
Abstract: Neurodevelopmental disorders (NDD) are complex and multifaceted diseases involving genetic and environmental sciences. Rapid developments in sequencing techniques have made it possible to identify new disease‐causing genes. Our study aimed to identify novel genes associated with NDDs. Trio whole‐exome sequencing was performed to evaluate potential NDD variants. We identified three unrelated patients with compound heterozygous DNAH14 variants. The detailed clinical information and genetic results of the recruited patients were obtained and systematically reviewed. Three compound heterozygous DNAH14 variants were identified as follows: c.6100C > T(p.Arg2034Ter) and c.5167A > G(p.Arg1723Gly), c.12640_12641delAA(p.Lys4214Valfs*7) and c.4811T > A(p.Leu1604Gln), andc.7615C > A(p.Pro2539Thr) and c.11578G > A(p.Gly3860Ser), including one nonsense, one frameshift, and four missense variants, which were not existent or with low minor allele frequencies based on the gnomAD database. The missense variants were assumed to be damaging or probably damaging by using multiple bioinformatics tools. Four of these variants were located in the AAA+ ATPase domain, while two were located in the C‐terminal domain. Most affected amino acids were highly conserved in various species. A spectrum of neurological and developmental phenotypes was observed, including seizures, global developmental delay, microcephaly, and hypotonia. Thus, our findings indicate that variants of DNAH14 could lead to previously unrecognized NDDs. Abstract : Genetics plays a substantial role in the etiology of neurodevelopmental disorders. By trio whole‐exome sequencing, three unrelated patients with a spectrum of neurological and developmental phenotypes carrying compound heterozygous variants in DNAH14 were identified, which indicated that variants in DNAH14 could lead to previously unrecognized neurodevelopmental disorders.